Pelatihan PLC dan Elektropneumatik untuk Meningkatkan Kompetensi Profesional Guru SMK Bidang Ketenagalistrikan: Pendekatan Revolusi Industri 4.0 - Ta`ali Ta`ali; Aswardi Mawardi; Doni Tri Putra Yanto (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
This study discusses efforts to improve one of the competencies of Vocational High School (SMK) teachers in the field of Electricity, namely professional competence, through the implementation of the Programmable Logic Control (PLC) and Electropneumatics training program. the training program is designed in the form of learning processes namely learning theory and practice that is shared into two main materials namely PLC and Electropneumatics. Both of these materials are one part of industrial automation material that needs to be understood by every teacher to be taught to students because vocational learning materials must be adaptive to the latest developments in science and technology. The latest development of this century is termed the Industrial Revolution 4.0. The subjects of this study are 20 teachers in the field of electricity in SMK Negeri 1 Bukittinggi. The results showed that after the implementation of the training program there is an increase in the professionalism of teachers in the field of industrial automation especially PLC and Electropneumatics indicated by the participants' posttest results which reached 85,6% graduation for the two materials. Thus, it can be concluded that PLC and Electropneumatics training for teachers can improve the professional competence of teachers in the field of industrial automation by the development of the industrial revolution 4.0